The Effect of Hyperemesis Gravidarum on Acceptance of Pregnancy and Quality of Life: A Comparative Study - Tahta, Tuğba; Yilmaz, Figen A. (Current Women's Health Reviews, 2023)
Objective: This study was conducted to determine the effect of hyperemesis gravidarum diagnosis in pregnant women on their acceptance of pregnancy and quality of life. Methods: This case-control study was conducted with 375 pregnancy 175 diagnosed with hyperemesis gravidarum (case group), 200 pregnant women with healthy pregnancy (control group), between July 2018 and February 2019, in Turkey. Data were collected with the Personal Information Form, World Health Organization’s Quality of Life Questionnaire Brief Version was used to ascertain quality of life and to determine adaptation to pregnancy, the “Prenatal Self-Evaluation Scale” was applied. Only the “Acceptance of Pregnancy” subdimensions were included in the study. Results: Pregnancy acceptance was found to be significantly lower in pregnant women with hyperemesis gravidarum than in healthy pregnant women. The quality of life levels of the pregnant women with hyperemesis gravidarum were found to be lower than those in the healthy pregnant women. Conclusion: Quality of life is affected by hyperemesis gravidarum. In addition, low quality of life and hyperemesis gravidarum negatively affect the acceptance of pregnancy. This result highlights that healthcare professionals should develop a strategy to improve the quality of life of women with hyperemesis and help them accept their pregnancy.
Keywords: the effect of hyperemesis gravidarum